SPACE REQUIREMENTS AND BUILDING FORM STUDIES FOR LOW INCOME HOUSING COMMUNITY - Rizaldi Lufti; Nia Suryani; Fery Mulya Pratama (Universitas Indraprasta PGRI, 2023)
The need for a house is still the main need for humans, namely as a place to live, a place to live, or a place of refuge. This need often does not go according to expectations because the need for housing has arisen but is not in line with adequate income or funds. The problem of housing for people who do not have the power to buy a house or commonly called low-income people (MBR) is difficult to solve. This phenomenon requires a study of housing for low-income people that comes with a flexible concept so that the house can follow the needs of its occupants so that at any time this house can be adjusted depending on which spaces are needed to adjust the life development of the occupants even with a relatively small plot area. This study was carried out by conducting a literature review and simple simulation with the minimum size and money polarity needed by every human being in living activities, so that a study can be initiated that produces residential design proposals that are applicable to the MBR. So that houses that have been subsidized by the government (the selling price is affordable for the MBR) are not easily sold, and the MBR are again homeless. From the results of the study conducted, it can be seen that the rooms that cannot be changed (permanent) are only rooms related to installation (service zones) such as bathrooms and kitchens, while spaces that can be changed flexibly according to needs such as family rooms and a mezzanine room so that all the space needs of the occupants can be accommodated even with a relatively small land size. This study was conducted to produce a residential design for MBR that adapts to their needs and can become a house they live in for a long time even though their space requirements change.